NON-BINARY GENDER IDENTITY DEVELOPMENT - Simavarangkul, Chantanit; Intarakamhang, Ungsinun; Peungposop, Narisara (Journal of Social Science and Cultural, 2024)
This research aims to explore the developmental process of gender identity in non-binary individuals. The study employs a life history research method, involving nine participants selected through snowball and purposive sampling methods. Data were collected through in-depth interviews and observational methods, utilizing semi-structured questions as a research instrument. The data were analyzed using the thematic analysis approach, comprising six steps guided by Braun and Clarke’s framework, facilitated by the computer program ATLAS.ti. The findings reveal two themes as follows: 1) the developmental stages of gender identity occur through four phases 1.1) The pre-exploration period including four sub-themes: lack of awareness regarding gender aspects, authentic gender expression before perceiving gender identity, being affected by gender norms, and perceiving gender non-conforming. 1.2) The exploration period includes four sub-themes: gender expression outside normative gender binary, participation in gender-diverse communities, seeking information about gender-related diversity, and gender affirmation. 1.3) Revelation of gender identity period includes two sub-themes: identity disclosure and comprehension of gender identity. 1.4) The gender actualization period encompasses three sub-themes: independence from societal expectations, support for social movements related to gender diversity, and pride in one’s identity. (2) The impacts experienced by individuals during their developmental stages, including two highlighted sub-themes: firstly, the impact of social expectations concerning concealing one’s authentic gender expression and detaching oneself from society. Secondly, the impact of expressing oneself outside gender binary norms.